2021
DOI: 10.1007/s40670-021-01332-9
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Student Outbound Mobility—Improving Students’ Cultural Competency Skills Online to Improve Global Health Without Travel

Abstract: Introduction Student outbound mobility is a major element in internationalization of medical education and global health education. However, this approach is often criticized, as it is inherently inequitable. Internationalization at home is a newer concept that aims to provide students with international skills and experiences without exchange travel. We report detailed outcomes of an international online program during the COVID-19 pandemic, which aimed to include acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The results showed that the international curriculum of medical education integrated into teaching reform is bene cial for students to understand the latest scienti c research and clinical progress in the world and can improve their communication ability with professionals and patients. This is similar to the results of some studies that indicate that students can improve abilities that were previously believed to only be improved by going abroad [11,12]. The method of online contact with international peers was proposed by Ostbye and his colleagues in 1995, but only a few studies have reported this method so far [13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
“…The results showed that the international curriculum of medical education integrated into teaching reform is bene cial for students to understand the latest scienti c research and clinical progress in the world and can improve their communication ability with professionals and patients. This is similar to the results of some studies that indicate that students can improve abilities that were previously believed to only be improved by going abroad [11,12]. The method of online contact with international peers was proposed by Ostbye and his colleagues in 1995, but only a few studies have reported this method so far [13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
“…History, agriculture, and military sciences, by contrast, accounted for less than 1%. The distribution of majors chosen by international students is relatively consistent with the popular majors chosen by Chinese college students ( Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 55%
“…The top three advantages of online learning were effectively reducing the risk of COVID-19 infection, saving living and commuting expenses, and saving commuting time, with the cumulative selection rate of 80, 69, and 69%, respectively. Online learning, where students are primarily at home, can effectively reduce the probability of COVID-19 infection by avoiding gatherings ( Wu et al, 2021 ). At the same time, since the price of necessities in Europe and the United States is much higher than that in mainland China, students can save a lot expenses.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen references were written with the purpose of proposing guidelines or recommendations related to anticolonial public health (see Table 1 for a breakdown of topic areas) 33–36 39–50. Sixteen articles described or evaluated educational approaches 37 38 45 48–60. Reference target audiences were health professions institutions or students (n=22), global public health institutions or students (n=15) and healthcare providers (n=3).…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al 2021 58 Structure of global health learning experiences perpetuates global power hierarchies and is inherently inequitable.…”
Section: Author Year Problem Solutionsmentioning
confidence: 99%